Analisis Pengaruh Tingkat Suku Bunga, Inflasi, Dan Nilai Tukar Rupiah Terhadap Jakarta Islamic Index (Jii) Periode Januari 2008 - Desember 2014 - Nurfitriyani, Putri; , Eni Setyowati, SE, M.Si; , Dr. Muhammad Muhtarom, MH (2016)
This research aims to determine the effect of Interest Rate (BIRATE), Inflation (INF), and Exchange Rate (KURS) to the Jakarta Islamic Index period January 2008 - December 2014. The data used in this research is secondary data in the form of monthly time series. Analysis model used in this research is quantitative analysis using Partial Adjustment Model (PAM) regression. The results indicates that all variabel simultaneously generated significant effect on the Jakarta Islamic Index (JII). In addition, the results of partial that interest rate and exchange rate did significantly influence the Jakarta Islamic Index (JII). In contrast, inflation had a did not significant effect on the Jakarta Islamic Index (JII).